Pembelajaran Tahfidz Al-Qur’an Metode Habituasi di Pondok Pesantren Hamalatul-Qur’an - Zainul Arifin (Prodi Ilmu Al Qur'an dan Tafsir, 2026)
This study discusses the habituation method of Qur’an memorization (tahfidz al-Qur’an) implemented at Hamalatul-Qur’an Islamic Boarding School in Jombang. The habituation method emphasizes oral skills and the development of consistent habits in memorizing the Qur’an. This research employs a qualitative approach. Data were collected through observation, interviews, and documentation. The data were analyzed through data reduction, verification, and analysis, while the validity of the data was ensured through triangulation. The findings indicate that the concept of the habituation method involves conditioning students (santri) to interact regularly with the Qur’an by reciting it according to established standards, thereby generating positive responses. This interaction is integrated into various daily activities, such as muraqabah, congregational prayers, and other religious practices. The method has both advantages and disadvantages. Its main advantage is that it enables students to memorize the Qur’an more easily and quickly. However, its drawback is that the repetitive nature of the activities may become monotonous, leading to boredom and a lack of motivation among students. Therefore, the boarding school management should develop more varied activities to prevent students from becoming bored.